Synthesis of an Alternating Polycation with the Dense 1,2,3-Triazole Backbone - Omae, Tomoki; Nakahata, Masaki; Kamon, Yuri; Hashidzume, Akihito (Synlett, 2024)
Polycations are an important class of water-soluble polymers because they form polyion complexes with DNA. Thus, the synthesis of polycations with controlled monomer sequences will be of increasing importance for the formation of well-defined polyion complexes. In this study, cationic homopolymer and alternating copolymer with the dense triazole backbone were synthesized by copper(I)-catalyzed azide–alkyne cycloaddition polymerization. The polycations obtained were characterized by potentiometric and turbidimetric titrations, and by complex formation with poly(acrylic acid).
Keywords: alternating copolymers; polycations; dense triazole backbone; copper(I)-catalyzed azide–alkyne cycloaddition; heterodimers